Protective behavior and SARS-CoV-2 infection risk in the population - Results from the Gutenberg COVID-19 study - Rieke Baumkötter; Simge Yilmaz; Daniela Zahn; Katharina Fenzl; Jürgen H. Prochaska; Heidi Rossmann; Irene Schmidtmann; Alexander K. Schuster; Manfred E. Beutel; Karl J. Lackner; Thomas Münzel; Philipp S. Wild (BMC, 2022)
Abstract Background During the SARS-CoV-2 pandemic, preventive measures like physical distancing, wearing face masks, and hand hygiene have been widely applied to mitigate viral transmission. Beyond increasing vaccination coverage, preventive measures remain urgently needed. The aim of the present project was to assess the effect of protective behavior on SARS-CoV-2 infection risk in the population. Methods Data of the Gutenberg COVID-19 Study (GCS), a prospective cohort study with a representative population-based sample, were analyzed. SARS-CoV-2 infections were identified by sequential sampling of biomaterial, which was analyzed by RT-qPCR and two antibody immunoassays. Self-reported COVID-19 test results were additionally considered. Information on protective behavior including physical distancing, wearing face masks, and hand hygiene was collected via serial questionnaire-based assessments. To estimate adjusted prevalence ratios and hazard ratios, robust Poisson regression and Cox regression were applied. Results In total, 10,250 participants were enrolled (median age 56.9 [43.3/68.6] years, 50.8% females). Adherence to preventive measures was moderate for physical distancing (48.3%), while the use of face masks (91.5%) and the frequency of handwashing (75.0%) were high. Physical distancing appeared to be a protective factor with respect to SARS-CoV-2 infection risk independent of sociodemographic characteristics and individual pandemic-related behavior (prevalence ratio [PR] = 0.77, 95% confidence interval [CI] 0.62-0.96). A protective association between wearing face masks and SARS-CoV-2 transmission was identified (PR = 0.73, 95% CI 0.55-0.96). However, the protective effect declined after controlling for potential confounding factors (PR = 0.96, 95% CI 0.68-1.36). For handwashing, this investigation did not find a beneficial impact. The adherence to protective behavior was not affected by previous SARS-CoV-2 infection or immunization against COVID-19. Conclusion The present study suggests primarily a preventive impact of physical distancing of 1.5 m, but also of wearing face masks on SARS-CoV-2 infections, supporting their widespread implementation. The proper fit and use of face masks are crucial for effectively mitigating the spread of SARS-CoV-2 in the population.